DETERMINATION OF ANTHOCYANINS, TOTAL PHENOLS AND ANTIOXIDANT CAPACITY OF RUBUS ROBUSTUS C. PRESL - Ramírez Revilla, Stamber Alvaro (2022)
Natural antioxidants, such as fruits and vegetables, can neutralize an excess of free radicals in the organism and prevent certain degenerative diseases. Blackberries are known to exhibit antioxidant properties, but this fruit is seldom consumed or commercialized in Peru. The objective of this research study was to determine the total anthocyanins (TA), total phenolic compounds (TPC) and antioxidant capacity of lyophilized Rubus robustus C. Presl (wild blackberries) in the region of Arequipa - Peru. The pH-differential method, the Folin- Ciocalteu method and the free radical 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) method were used to this end. Results showed a TA content of 52 ± 1.86 mg cyanidin 3-glucoside/100 g of lyophilized Rubus robustus C. Presl. Furthermore, the TP content was of 219.11 ± 8.23 mg gallic acid/100 g of the lyophilized fruit. The percentage of DPPH discoloration of two samples (1.0 and 2.0 mg/mL) of the lyophilized fruit was determined, obtaining a percentage of 35.89 ± 4.43 and 67.23 ± 3.30%, respectively. The IC50 value found was 1.5 mg/mL. Wild blackberries in Arequipa, Peru were therefore shown to possess an antioxidant capacity, so a diet rich in this type of fruit should be promoted as a nutraceutical.